(untitled) (International Journal of Engineering and Computer Science, 2017)
The favour of wireless networks over wired networks has been increasing for the past few decades. The flexibility and accountability brought by wireless networks makes it preferable for several applications. In this midst all the present-day wireless networks, Mobile Ad hoc network (MANET) is among the most important types having distinctive applications.Each node in the Manet has a wireless interface to Communion with each other. In the Propone system adaptive acknowledgement approach (AACK) Digital signature algorithm is used which increases causes the network overhead if more malicious node involved. Thus system is used with Rijndael algorithms as a session key cryptography to reduce the network overhead caused by digital signatures in AACK. It scope of hybrid encryption is combination of Rijndael algorithm and RSA for the acknowledgement packets